Efeito da temperatura e do hospedeiro na biologia do ácaro-rajado, Tetranychus urticae Koch (Acari: Tetranychidae) - Bertollo, Étel Carmen (2007)
The incidence of mites, especially of the twospotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), has increased significantly in culture of soybean (Glycine max L.), in south of Brazil. Basic information about the biology of this species for local conditions, are scarce. The temperature and the host are factors that more influences in the biology of mites. Experiments were carried out under controlled conditions of laboratory (relative humidity of 50 ± 10 % and photoperiod 12 hours) aiming to evaluate the effect of temperature and host in the biology of T. urticae. Bioclimatic chambers at 15, 20, 25 e 30ºC were used to study of temperature, concluding that temperature affect duration of developmental times, longevity of females, and oviposition period, decreasing with increase temperature among 15 and 30ºC and in egg-laying capacity (females unmated) and oviposition rhythm. The egg-laying capacity is highest at 20ºC, in females mated as unmated. Independently of the temperature, there is not difference in duration of developmental time from egg to adult period among males and females unmated, and in longevity among individuals mated and unmated. The threshold temperature and thermal constant estimated for egg to adult period is 11,0ºC and 126,7 day-degrees (GD). The temperature promotes alterations in duration of preoviposition, oviposition and postovipostion periods of mated females and in longevity of males and females mated, decreasing with increase temperature, at 15ºC. The temperature affect survivorship of eggs, immature phases and adults mated, which is smaller to 15ºC. The evaluation of hosts (cuban jute, hairy beggartick and soybean) in the biology of T. urticae, temperature of 25 ºC, it allowed to conclude that the host affects duration of immature phases and egg-adult period (embryonic developmental + post-embryonic), in which hairy beggartick provides a smaller velocity of development. The host affects longevity of males, that it is higher in hairy beggartick, in relation to soybean. The host also influences on survivorship of development phases and adult, which is higher in soybean. The longevity of males is higher than females, in hairy beggartick